2019
DOI: 10.1038/s41598-019-54399-1
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source Remote Gait Analysis: A Post-Surgery Patient Monitoring Application

Abstract: Critical to digital medicine is the promise of improved patient monitoring to allow assessment and personalized intervention to occur in real-time. Wearable sensor-enabled observation of physiological data in free-living conditions is integral to this vision. However, few open-source algorithms have been developed for analyzing and interpreting these data which slows development and the realization of digital medicine. There is clear need for open-source tools that analyze free-living wearable sensor data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…The majority of studies (80%) developed subject-specific models and only 33% of studies explored task extrapolation. The latter may be less of a barrier to implementation since in practice task identification will likely be a part of the pipeline for automated analysis [91], in which case highly accurate activity classification models are required [92]. Thus, task specific models could be selected following task identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies (80%) developed subject-specific models and only 33% of studies explored task extrapolation. The latter may be less of a barrier to implementation since in practice task identification will likely be a part of the pipeline for automated analysis [91], in which case highly accurate activity classification models are required [92]. Thus, task specific models could be selected following task identification.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sEMG for remote monitoring is less common than accelerometry and has been used primarily for quantifying indices of physical activity [94,95,96,97]. Recent efforts have estimated muscle activation time-series during walking using methods similar to those used to estimate muscle force using Hill-type muscle models [8,91,98]. This pre-processing step was used by several reviewed papers suggesting they may be practically deployed.…”
Section: Discussionmentioning
confidence: 99%
“…The foot-ground contact and GP muscle synergy function models assumed walking gait. This would not be problematic for remote monitoring as walking activity is identified in the processing pipeline [2]. However, analysis of other tasks would require development of other task-specific models.…”
Section: Discussionmentioning
confidence: 99%
“…REMOTE patient monitoring, enabled by advances in wearable technology and algorithms for human movement analysis, promises to improve the assessment and treatment of musculoskeletal disease [1]. Recent work quantifying stride-by-stride gait mechanics at segment-, joint-, and muscle-specific levels has shown that these variables may provide more sensitive measures of patient health than the more typical gross measures of physical activity [2], [3]. Despite these advances, many of the most clinically relevant variables have yet to be observed outside of controlled, laboratory environments.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the variables used for model building were collected in a single session, which although reflected a typical clinical assessment scenario, may not reflect normal movement behaviour in daily living. With more advance wearable sensor technology emerging which allows remote biomechanics analysis [49], the methods employed presently can be exploited to yield statistical models which have greater ecological validity, and ultimately better personalized predictive accuracy. Third, we did not include age as a predictor during model building even though individuals with LBP and rmLBP were significantly older than controls.…”
Section: Discussionmentioning
confidence: 99%